Novel Unsaturated Intermediates (Aldehyde, Polyolefin, Pheromone and Fatty Acid) Synthesized using Wittig Reaction - Hussein Habeeb Mustafa (Journal of Global Pharma Technology, 2018)
In this study novel unsaturated compounds could be prepared with the required skip-conjugated (Z,Z)-double bonds configuration using a traditional Wittig reaction. This reaction depends on a coupling of aldehydes with phosphonium salt. Must products do not appear to have been prepared before, and these products were diagnosed by using NMR spectrum, infrared (IR) and mass spectrometer techniques. It is concluded that these products could widely be used as a fatty acid and a useful intermediates in the synthesis of pheromones instead of insecticides, and several chemical reactions.Keywords: Witting reaction, Unsaturated fatty acid, Skip-conjugated alkenes, Pheromone.